Peri-Implant Crestal Bone Loss: A Putative Mechanism - Yuko Ujiie; Reynaldo Todescan; John E. Davies (Hindawi Limited, 2012)
Purpose. The immunological mechanisms of peri-implant crestal bone loss have, hitherto, not been elucidated. We hypothesized that bacterial products from the microgap cause upregulation of cytokines in otherwise healthy peri-implant cells, which results in osteoclast formation and, ultimately, in bone resorption. Materials and Methods. We used RT-PCR and ELISA to assay mediators of osteoclastogenesis in rat and human macrophages (r-and hMO); bone marrow derived stromal cells (r-and hBMCs); and human gingival fibroblasts (hGF)-with or without stimulation by LPS. TRAP positive multinucleate cells were assessed for their resorptive ability. Results. We show that IL-1α, IL-1β, and IL-6 were expressed by all examined cell types, and TNF-α was upregulated in hGF. Secretion of IL-1α and IL-1β proteins was stimulated in hMO by LPS, and IL-6 protein secretion was highly stimulated in hBMCs and hGF. Both LPS and RANKL stimulated macrophages to form osteoclast-like TRAP positive cells, which resorbed calcium phosphate substrates. Conclusion. Taken together, the results of our study support the hypothesis that bacterial endotoxins upregulate enhanced mediators of osteoclastogenesis in resident cells found in the healthy peri-implant compartment and that the local synergistic action of cytokines secreted by such cells results in the genesis of resorptively active osteoclasts.